Transcription elongation control by the 7SK snRNP complex: Releasing the pause. Issue 16 (17th August 2016) - McNamara, Ryan P.; Bacon, Curtis W.; D'Orso, Iván
ABSTRACT: The ability for the eukaryotic cell to transcriptionally respond to various stimuli is critical for the overall homeostasis of the cell, and in turn, the organism. The human RNA polymerase II complex (Pol II), which is responsible for the transcription of protein-encoding genes and non-coding RNAs, is paused at promoter-proximal regions to ensure their rapid activation. In response to stimulation, Pol II pause release is facilitated by the action of positive transcription elongation factors such as the P-TEFb kinase. However, the majority of P-TEFb is held in a catalytically inactivate state, assembled into the 7SK small nuclear ribonucleoprotein (snRNP) complex, and must be dislodged to become catalytically active. In this review, we discuss mechanisms of 7SK snRNP recruitment to promoter-proximal regions and P-TEFb disassembly from the inhibitory snRNP to regulate 'on site' kinase activation and Pol II pause release.